2007
DOI: 10.1007/s11244-007-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-way catalyst emissions control technologies for spark-ignition engines—recent trends and future developments

Abstract: Exhaust gas emissions from passenger cars with traditional gasoline engines have been markedly reduced over the three decades since the introduction of catalysts. The first oxidation catalysts were superseded by two-catalyst three-way systems that were followed by single three-way catalysts (TWCs). The first Pt/Rh-based TWCs formulations were refined by incorporating increasingly thermally stable ceria-based components to keep the surface composition close to stochiometric during exhaust gas composition fluctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…1 CH 4 conversion profiles for Pd/ACZ and Pd/A under simulated stoichiometric conditions of natural gas engines during two heating-cooling cycles 850°C reveals that either CH 4 reforming or reverse water gas shift is possibly at work above 370°C. Both NO reduction by CH 4 and CH 4 (steam) reforming have been mentioned as possible concurrent reactions to CH 4 oxidation responsible for CH 4 removal from the exhaust [12]. The present data confirm that direct CH 4 oxidation is not the only reaction contributing to this process under dry stoichiometric conditions.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…1 CH 4 conversion profiles for Pd/ACZ and Pd/A under simulated stoichiometric conditions of natural gas engines during two heating-cooling cycles 850°C reveals that either CH 4 reforming or reverse water gas shift is possibly at work above 370°C. Both NO reduction by CH 4 and CH 4 (steam) reforming have been mentioned as possible concurrent reactions to CH 4 oxidation responsible for CH 4 removal from the exhaust [12]. The present data confirm that direct CH 4 oxidation is not the only reaction contributing to this process under dry stoichiometric conditions.…”
Section: Resultssupporting
confidence: 79%
“…Figure 1 shows that such characteristics are maintained under stoichiometric conditions (CH 4 , CO, NO x and O 2 ) of CH 4 oxidation on the model Pd/ACZ three-way catalyst (TWC). The MS signals of the pollutants are provided in Figure S1.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Although bicelles have been suggested as templating agents for the growth of nanomaterials, prior to our recent study 11 no successful examples had been reported, partially because of the difficulties in obtaining high yields of bicelles. 3,4 In an earlier study, 11 we investigated the synthesis of platinum materials to demonstrate the templating ability of bicelles, since platinum is technologically important for applications in sensing, 12,13 reduction of tailpipe emissions, [14][15][16] electrocatalytic energy conversion in proton exchange membrane (PEM) fuel cells, [17][18][19] and renewable energy production in artificial photosynthesis and water-splitting devices. 20,21 Our previous study primarily focused on the synthesis and structural characterizations of the platinum nanowheels obtained in the presence of bicelles.…”
Section: Introductionmentioning
confidence: 99%